Causal associations of brain structure with bone mineral density: a large-scale genetic correlation study - Guo, Bin; Wang, Chao; Zhu, Yong; Liu, Zhi; Long, Haitao; Ruan, Zhe; Lin, Zhangyuan; Fan, Zhihua; Li, Yusheng; Zhao, Shushan (Bone Research, 2023)
In this study, we aimed to investigate the causal associations of brain structure with bone mineral density (BMD). Based on the genome-wide association study (GWAS) summary statistics of 1 325 brain imaging-derived phenotypes (BIDPs) of brain structure from the UK Biobank and GWAS summary datasets of 5 BMD locations, including the total body, femoral neck, lumbar spine, forearm, and heel from the GEFOS Consortium, linkage disequilibrium score regression (LDSC) was conducted to determine the genetic correlations, and Mendelian randomization (MR) was then performed to explore the causal relationship between the BIDPs and BMD. Several sensitivity analyses were performed to verify the strength and stability of the present MR outcomes. To increase confidence in our findings, we also performed confirmatory MR between BIDPs and osteoporosis. LDSC revealed that 1.93% of BIDPs, with a false discovery rate (FDR) < 0.01, were genetically correlated with BMD. Additionally, we observed that 1.31% of BIDPs exhibited a significant causal relationship with BMD (FDR < 0.01) through MR. Both the LDSC and MR results demonstrated that the BIDPs “Volume of normalized brain,” “Volume of gray matter in Left Inferior Frontal Gyrus, pars opercularis,” “Volume of Estimated Total Intra Cranial” and “Volume-ratio of brain segmentation/estimated total intracranial” had strong associations with BMD. Interestingly, our results showed that more left BIDPs were causally associated with BMD, especially within and around the left frontal region. In conclusion, a part of the brain structure causally influences BMD, which may provide important perspectives for the prevention of osteoporosis and offer valuable insights for further research on the brain-bone axis.